Bolivia : Staff Report for the 2003 Article IV Consultation, First Review Under the Stand-By Arrangement, and Request for Waiver of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
Macroeconomic and financial vulnerabilities have intensified in recent years. Bolivia has adopted a program to stabilize the situation, and the program is broadly on track. Monetary policy is appropriately geared to support a gradual build-up of international reserves while ensuring needed liquidity for the financial system. A comprehensive strategy is being developed for the financial and corporate sectors. Executive Directors welcome the government's progress toward a medium-term economic program that will foster a higher rate of sustained growth and reduce poverty.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet